Order effects in transitive inference: does the presentation order of social information affect transitive inference in social animals? - Hotta, Takashi; Jordan, Lyndon A.; Takeyama, Tomohiro; Kohda, Masanori (Frontiers in Ecology and Evolution, 2015)
Transitive inference (TI) is the ability to infer social relationships between individuals (e.g., if A < B and B < C, then A < C), and has been documented in a variety of vertebrates. Many studies of TI use the task of inferring social dominance, where a subject animal A first directly interacts with B (e.g., A subordinate to B: A < B), and then indirectly observes the interaction of B and an unknown C (B < C), using both direct and indirect information to infer its own relationship with C (i.e., A < C). However, order effects are known to influence learning, especially in complex scenarios, and we have little understanding of the effects of presentation order in transitive inference. Here we show that the cichlid Julidochromis transcriptus can use TI to correctly assess social relationships when information is presented in the order opposite to that most commonly employed in studies of TI. We find that focal individuals (A) can transitively infer their relationships with an unknown individual (C) when initially given indirect experience (i.e., eavesdropping that B < C) and then given direct experience (A < B). We conclude that J. transcriptus can infer social relationships when experiencing first indirect and then direct social information. We suggest that in this and many other species, transitive inference may occur in either presentation order, and future studies of TI should account for order effects of social information.